(untitled) (Fiep Bulletin - online, 2014)
Professor Otañez explains that organizations related to Physical Education in Latin America started with FIEP in 1923; in 1949, the Physical Education International Association, in 1952, the ICHPER – organization for Health, Physical Education, Sports and Dance, and in 1958, the AIESEP – Association Internationale d’Éducation Physique. He presents a description of the origin and development of FIEP in Latin America and its current situation in this continent. He concludes by remarking that Brazil plays a leading role as FIEP leading country in Latin America, seconded by Argentina, Mexico and Paraguay.